EFEKTIVITAS PENYULUHAN KB IUD DENGAN MEDIA VIDEO ANIMASI TERHADAP TINGKAT PENGETAHUAN DAN SIKAP PASANGAN USIA SUBUR (PUS) DI DESA PUCUNG KABUPATEN PEKALONGAN - fitri nur shofa; Is Susiloningtyas; Endang Susilowati (Politeknik Kesehatan Kemenkes Bengkulu, 2023)
ABSTRACT Problems: The IUD is a long-term contraceptive method that has a very high effectiveness of 0.6-0.8 pregnancies of 100 women in the first year with 1 failure in 125 to 170 pregnancies. The aim of the research: Knowing the effectiveness of IUD family planning counseling with animated video media on increasing the knowledge and attitudes of Couples of Reproductive Age (PUS) in Pucung Village, Pekalongan Regency. Research methods: The design of this research is pre experiment with one group pretest-posttest. The number of samples used was 86 respondents in Pucung Village, Pekalongan Regency using the Purposive Sampling technique. The data analysis used was Univariate and Bivariate analysis using the Wilcoxon Test. Results: Counseling on IUD family planning with animated video media is effective in increasing the knowledge and attitudes of PUS mothers in Pucung Village, Pekalongan Regency. Asymp value. Sig 0.000p<0.05. Conclusion: Counseling on IUD family planning with animated video media is effective in increasing the knowledge and attitudes of PUS mothers in Pucung Village, Pekalongan Regency. Suggestion: It is hoped that the people of Pucung Village, Pekalongan Regency, will continue to provide information, either through individual or group counseling Keywords: Animation Video Media Counseling, KB IUD, PUS